Trait-Based Emotional Intelligence, Body Image Dissatisfaction, and HRQoL in Children - Pollatos, Olga; Georgiou, Eleana; Kobel, Susanne; Schreiber, Anja; Dreyhaupt, Jens; Steinacker, Jürgen M. (Frontiers in Psychiatry, 2020)
Background: Body image dissatisfaction (BID) is related to an increased risk for various health issues including descreased health-related quality of life (HRQoL), the development of problematic eating behaviors and obesity. Previous research indicates that emotional intelligence (EI) is one important factor related to BID in adults. Whether this is the case in children, remains yet unknown. Taking this into consideration, the aim of this study was to explore the relationship between BID and trait based emotion intelligence (TEI) as well as HRQoL in female and male primary school children. Materials and methods: TEI and BID were assessed via self-reports as well as HRQoL via parental reports in a large sample of 991 primary school children (429 girls) within the “Baden Württemberg Study”, which evaluated the effectiveness of the health prevention programm “Join the Healthy Boat” in Southwestern Germany. Results: Our findings demonstrated an interrelation between higher levels of TEI and lower levels of BID among girls and boys. Low intrapersonal abilities (as a subscale of TEI) qualified this effect in girls, while in boys this was the case for low adaptability. Furthermore, a positive association was found between better HRQoL, better intrapersonal and stress management abilites (subscales of TEI) and lower BID, as reflected by parental and self-reports. Conclusions: Our results reveal an interconnectivity between TEI, BID and better HRQoL in female and male primary school children. Although the observed correlations were rather small, they nervertheless support the idea that TEI consists a key-factor for the self-regulation of health-related behavior. Prevention programs could benefit from including processes, that sough to improve aspects of emotional intelligence such as: intrapersonal, interpersonal abilities and adaptability, as an effort of preventing problematic habits or lifestyles that could lead to disordered eating behaviors as well as to obesity in middle childhood.